Minutes : 18 September 1939
1939-10-09 038-0073-003 MINUTES OF A MEETING OF THE BASQUE ADMINISTRATIVE COMMITTEE HELD AT 30, ECCLESTON STREET, S.W.1. ON MONDAY SEPTEMBER 18. at 4 p.m. Present: Miss Eleanor Rathbone (in the chair) Dr. Betty Morgan Mr. R.G. Thackrah Mr. Fuller Bryant Miss Edith Pye Dr. Camps Miss Smith Mr. Hans Siebert Pat Rimel 1. FINANCIAL STATEMENT It was reported that the Basque Children's Committee no longer had any funds at their disposal centrally but that transfers sufficient to meet the expenditure for a few weeks longer were being made from the National Joint Committee. 2. CAMPAIGN REPORT A circular had been sent out to all Basque Children's Homes and Committees suggesting lines of organisations under war conditions. The circular is attached to the minutes. Local National Joint Committee branches and Spanish Aid committees had also been asked to find offers of hospitality for children who would still have to remain in this country and also to assist in finding work for older boys and girls. 3. REPORT FROM FOREIGN OFFICE Dr. Morgan reported that the Foreign Office was pressing for the return of all Basque Children. The matter would have to be considered in detail at the meeting of the Basque Children's Committee on September 21st. It was agreed to recommend the children whose parents were not in Spain should not be repatriated. 4. REPORT ON HOMES Mr. Fuller Bryant reported that Aylesbury House would have to close at the end of October or in the first week of November. Unless repatriation had taken place before the closing of the Home it would be necessary to find accomodation for all the Aylesbury children. Dr. Morgan reported that if the Theydon Bois Home could be kept open there would be a sufficient number of vacancies. Agreed to discuss this matter in full detail when the result of the negotiations with the Foreign Office was known. 5. REPORT FROM DR. CAMPS Dr. Camps reported on her visits to Colchester, Cambridge and Wickham Market. The reports were discussed and accepted. There being no other business the meeting then closed. pr. 9.10.39. 292/946/38/73(III)